Effective deformation properties of fibrous composite materials under physically nonlinear deformation of components - Khoroshun, L.P.; Shikula, E. N. (Reports of the National Academy of Sciences of Ukraine, 2016)
A model of nonlinear deformation of fibrous composite materials under physically nonlinear deformation of components is formulated. Algorithms of determination of effective deformative properties of fibrous composite materials are constructed. Influence of a nonlinearity of the deformation of components on the effective deformative properties of fibrous composite materials is investigated.